2017
DOI: 10.1016/j.jcot.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Ankle arthrodesis—Open versus arthroscopic: A systematic review and meta-analysis

Abstract: The best available evidence demonstrates that arthroscopic ankle fusion may be associated with a higher fusion rate, shorter tourniquet time, and shorter length of stay compared to open ankle fusion. We found no significant difference between two groups in terms of infection rate, overall complication rate, and operation time. The best available evidence is not adequately robust to make definitive conclusions. Long-term results of the comparative efficacy of arthroscopic ankle fusion over open ankle fusion are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
26
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 18 publications
6
26
1
Order By: Relevance
“…Regarding the rate of fusion, the meta-analysis showed that there was a remarkable difference between arthroscopic arthrodesis and open surgery, and the data support the most recent meta-analysis by Honnenahalli et al [3] Patients who underwent arthroscopic arthrodesis had a higher fusion rate than those who underwent open surgery. In arthroscopic arthrodesis, the soft tissue envelope is disrupted to a minimum degree, which enables the major functions of soft tissues close to the surgical site.…”
Section: Inferences and Implicationssupporting
confidence: 70%
See 3 more Smart Citations
“…Regarding the rate of fusion, the meta-analysis showed that there was a remarkable difference between arthroscopic arthrodesis and open surgery, and the data support the most recent meta-analysis by Honnenahalli et al [3] Patients who underwent arthroscopic arthrodesis had a higher fusion rate than those who underwent open surgery. In arthroscopic arthrodesis, the soft tissue envelope is disrupted to a minimum degree, which enables the major functions of soft tissues close to the surgical site.…”
Section: Inferences and Implicationssupporting
confidence: 70%
“…First, it was noted that there was no significant difference in days to union, which is contrary to previous studies. [3] Patients who underwent arthroscopic arthrodesis did not have a shorter time to union than those who experienced open surgery.…”
Section: Strength Of the Systematic Reviewmentioning
confidence: 93%
See 2 more Smart Citations
“…Honnenahalli et al demonstrates that arthroscopic ankle fusion may be associated with a higher fusion rate, shorter tourniquet time, and shorter length of stay compared to open ankle fusion [20].…”
Section: Discussionmentioning
confidence: 99%